Antibacterial properties of ginger rhizome - Ashraf, Shafia; Shams , Rafeeya (Journal of Postharvest Technology, 2021)
Ginger rhizome (Zingiber officinale), is an essential plant based product consumed as spice and can be used as naturopathy due to its  potential antimicrobial activity against various pathogenic microbes and is also used in various food industries and traditional medicine. In this  study, the antimicrobial potential of ginger was analyzed against Gram -ve Escherichia coli and Gram +ve Enterococcus faecalis and  Staphylococcus aureus. Analysis of the results of sensitivity tests (disc diffusion assays) indicated each of the microorganisms to be  completely inhibited. The formation of zones of inhibition indicated that the spice tested was effective as an antimicrobial agent when  screened. Zones of inhibition (greater than 30 mm in diameter were obtained during positive disc diffusion assaying. Analysis of the results  concluded that the active compounds present in the Ginger were effective against tested micro-organisms and may be used to treat bacterial  infections. This could be an alternative treatment to antibiotics for one or all of the microbial species investigated and in so doing allow the  healing powers of spices to be acknowledged. The observations of such inhibition zones were comparatively significant and demonstrated the  potential use of these Ginger as antimicrobial agents with an efficacy that can be compared to that of the already recognized and widely used  antibiotic, neomycin.
Keywords: Ginger; antimicrobial,; zone of inhibition; antibiotics,; extraction; microorganism